Adolescent Life Satisfaction Explained by Social Support, Emotion Regulation, and Resilience - Azpiazu Izaguirre, Lorea; Fernández, Arantzazu Rodríguez; Palacios, Eider Goñi (Frontiers in Psychology, 2021)
Adolescence is a stage characterized by many biological and psychosocial changes, all of which may result in a decrease in subjective well-being. It is therefore necessary to identify those factors that contribute to increased life satisfaction, in order to promote positive development among young people. The aim of this study is to examine the dynamics of a set of variables that contribute to life satisfaction. A total of 1188 adolescents (aged between 12-16 years) completed the Perceived Social Support from Family and Friends and Perception of the School Environment Questionnaires, the Trait Meta Mood Scale, Connor-Davidson Resilience Scale-10 and Satisfaction with Life Scale for social support, emotion regulation, resilience and life satisfaction. By applying structural equation modeling (SEM), the results reveal a direct prediction of family support, emotion regulation and resilience on life satisfaction. Support from friends and emotion regulation were also found to explain resilience, and support from family and teachers was found to predict emotion regulation. In conclusion, emotion regulation and social support were found to indirectly affect life satisfaction among adolescents through resilience. The theoretical and practical implications of these results are discussed.